The Trình Tường house of the Bố Y People in Vietnam: A Study on Cultural Heritage and Traditional Architecture - Viet, Tran Quoc; Thom, Le Thi; Kha, Pham Trang; Anh, Do Tuan; Nhi, Tran Yen (Journal of Ecohumanism, 2024)
The Trình Tường house (similer Earthen-Walled house), a distinctive architectural form of the Bố Y people in Vietnam, has embodied both cultural and spiritual values, reflecting their ethnic identity. However, modernization, climate change, and the development of tourism have placed immense pressure on the preservation of this traditional architecture. This paper aims to analyze the cultural and architectural values of the Trình Tường house in the modern context while proposing solutions for its preservation and promotion as a cultural heritage. The research was based on qualitative methods, including field observation, semi-structured interviews with Bố Y community members, and comparative analysis of traditional architecture from other ethnic minorities in Southeast Asia and worldwide. The findings revealed that the Trình Tường house was not only a physical structure but also a cultural and spiritual symbol, connecting people with nature and belief systems. However, pressures from modernization and climate change have compromised the sustainability of this architecture. The study contributes to cultural ecology theory and offers specific policy recommendations for preserving the Trình Tường house, ensuring the Bố Y people’s cultural identity, and paves the way for future research on traditional architectural conservation in the current context.